VD_FINDINFO ML / 2012 / 289 vom 26. November 2012 - VD Tribunal cantonal (2012)
DROIT D'ÊTRE ENTENDU, NOTIFICATION IRRÉGULIÈRE, NULLITÉ | 84 al. 2 LP, 107 al. 2 CPC (CH), 136 CPC (CH), 138 al. 1 CPC (CH), 327 al. 3 let. a CPC (CH), 53 al. 1 CPC (CH)